1998
DOI: 10.1016/s0014-5793(98)00892-8
|View full text |Cite
|
Sign up to set email alerts
|

Cselp functions as the nuclear export receptor for importin α in yeast

Abstract: CSEI is essential for yeast cell viability and has been implicated in chromosome segregation. Based on its sequence similarity, Cselp has been grouped into the family of importin like nucleocytoplasmic transport receptors with highest homology to the recently identified human nuclear export receptor for importin ~, CAS. We demonstrate here that Cselp physically interacts with yeast Ran and yeast importin tx (Srplp) in the yeast two-hybrid system and that recombinant Cselp, Srplp and Ran-GTP form a trimeric com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 70 publications
7
70
0
Order By: Relevance
“…2A). This is con-sistent with results showing that Gsp1p, Cse1p, and Kap60p form an exportin-cargo complex (13)(14)(15), which presumably translocates across the NPC by interacting with FG Nups.…”
Section: Identification Of Nup159p-and Cse1p-interacting Proteinssupporting
confidence: 79%
“…2A). This is con-sistent with results showing that Gsp1p, Cse1p, and Kap60p form an exportin-cargo complex (13)(14)(15), which presumably translocates across the NPC by interacting with FG Nups.…”
Section: Identification Of Nup159p-and Cse1p-interacting Proteinssupporting
confidence: 79%
“…Importin ␤ was expressed and purified as described previously (26). GSTimportin ␣ and GST-A3-importin ␣ were expressed as described elsewhere (40).…”
Section: Methodsmentioning
confidence: 99%
“…Our in vitro data showing that the A3 mutations do not appear to have a direct impact on the binding of Cse1p to importin ␣ suggest that this defect is due to impaired release of cargo in the nucleus. Previous work has shown that the Cse1p/CAS association with importin ␣ does not depend on the N-terminal domain (40,48). In fact, the Cse1p/ CAS binding site has been mapped to the C terminus of human importin ␣ (21).…”
Section: Table II Binding Of Importin ␣ Proteins To Nls-cargomentioning
confidence: 96%
“…We explored the possibility that CSE1 and SMC4 could play roles in regulating DNA replication. CSE1 is responsible for the nuclear shuttling of the nuclear transporter importin ␣ (Hood and Silver, 1998;Kunzler and Hurt, 1998;Solsbacher et al, 1998) and a role for CSE1 in mitosis (but not in S phase) has been described (Xiao et al, 1993;Schroeder et al, 1999). We synchronized cells in G1, released them into the cell cycle after shut-off of TetO 7 -CSE1, and measured the DNA contents of the cells by flow cytometry ( Figure 6A).…”
Section: S Phasementioning
confidence: 99%